PENGARUH PENERIMAAN TEKNOLOGI TERHADAP KEPUASAN KONSUMEN PENGGUNA APLIKASI ACCESS BY KAI - Samuel, Soni (Gunahumas, 2024)
The high level of population mobility in Indonesia causes train ticket sales to increase. The higher and faster sales of train tickets also require the development of technology that helps the process of providing people's needs in buying train tickets. This technology development can take the form of digital applications that aim to increase sales and consumer satisfaction. Access by KAI is the only official application made by PT. KAI that sells train tickets and provides train travel services to the public. However, Access by KAI application still has problem, namely the number of active application users is still stagnant. This research aims to analyze technology acceptance factors based on conceptualization models from previous literature that influence people's intention to use the Access by KAI application and its effect on consumer satisfaction. These factors include perceived ease of use, perceived usefulness, motivation, and experience. This research uses a quantitative approach with a research instrument in the form of a questionnaire given to 100 Access by KAI users. The questionnaire data that has been collected will be analyzed using IBM SPSS 25 software. Based on the research results, the variables perceived ease of use, motivation and experience have a positive and significant effect on consumer satisfaction, while the variable perceived usefulness has no effect on consumer satisfaction. Overall, technology acceptance has strong and significant on consumer satisfaction.